Implementação dos indicadores do SIAMI desktop para o SIAMI web - TEODORO NETO, José Caruzo; COSTA, Bruno Cesar Alves; GOMES, Hálex Viotto; SASS, Glaucia Gabriel; FACCENDA, Odival; ALVARENGA, Márcia Regina Martins (ANAIS DO ENIC, 2017)
-